Predictive values of serum FGF21 and SCUBE-1 in predicting major adverse cardiovascular events in maintenance hemodialysis patients - Xu Mei; Wang De-qin; Weng Li-na (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the predictive values of serum fibroblast growth factor 21（FGF21） and signal peptide， CUB and EGF-like domain-containing protein 1（SCUBE-1） in predicting major adverse cardiovascular events（MACEs） in maintenance hemodialysis（MHD） patients.MethodsA total of 164 MHD patients admitted to our hospital from February 1， 2020 to February 28， 2023 were regarded as the observation group. The patients were followed up for 1 year and separated into an occurrence group （117 cases） and a non-occurrence group （47 cases） based on whether they had MACEs. A total of 164 healthy individuals who underwent physical examinations were as the control group. Enzyme linked immunosorbent assay （ELISA） was applied to detect serum FGF21 and SCUBE-1 levels. Multivariate Logistic regression was employed to analyze the influencing factors of MACE in MHD patients. The receiver operating characteristic （ROC） curve was used to analyze the predictive values of serum FGF21 and SCUBE-1 in MACEs of MHD patients.ResultsSerum FGF21 ［（39.67 ± 5.54） ng/L vs （30.33 ± 3.21） ng/L］ and SCUBE-1 ［（33.28 ± 4.41） μg/L vs （25.19 ± 2.68） μg/L］ in the observation group were significantly higher than those of the control group （P<0.05）. Serum FGF21 ［（44.94 ± 4.52） ng/L vs （37.55 ± 4.43） ng/L］， SCUBE-1 ［（36.86 ± 3.87） μg/L vs （31.84 ± 3.74） μg/L］， history of diabetes （80.85% vs 25.64%） and LDL-C［（3.26 ± 0.36） mmol/L vs （2.89 ± 0.30） mmol/L］ in the occurrence group were significantly higher than those in the non-occurrence group（P<0.05）. FGF21 and SCUBE-1 were influencing factors for the occurrence of MACEs in MHD patients （P<0.05）. The area under the curve （AUC） of serum FGF21 and SCUBE-1 in predicting MACEs was 0.881 and 0.823， respectively， which of their combination for MACE was 0.926. The combination of the two was better than that of the individual prediction （Z combination - FGF21=2.024， Z combination - SCUBE-1=3.082， P=0.043， and 0.002）.ConclusionSerum levels of FGF21 and SCUBE-1 are obviously elevated， which are risk factors for MACEs in MHD patients. The combination of the two has high predictive value for MACE in MHD patients.